Стан, проблеми та перспективи формування ринку інтелектуальних послуг - Сторожук, O. B.; Storozhuk, О. (КНТУ, 2013)
В статті проаналізовано сучасний стан, проблеми та перспективи формування ринку інтелектуальних послуг в Україні. Розглянуто практичні аспекти формування регіонального ринку інтелектуальних послуг на прикладі Кіровоградської області. Обгрунтовано пропозиції щодо активізації формування ринку інтелектуальних послуг в Україні. The purpose of article is research state and problems of Ukraine intellectual services market forming and development. The author analyzes and identifies the market prospects of intellectual services in Ukraine. Practical aspects of intellectual services market formation as an example of Kirovograd region considered. Innovative development support of the economy is absent. Population level profits is low. Estimation of the intellectual labour role is low. It does not give the intellectual services market development. Prospects of forming activization of Ukraine market intellectual services are presented. Ukraine market intellectual services in the process of formation. The need for some kinds of intellectual services increases in Ukraine (IT-consulting, scientific and technical services, advertising).
State, problems and perspectives of intellectual services market forming
Keywords: інтелектуальні послуги; ринок; проблеми; перспективи; intellectual services; market; problems; perspectives